O fim da picada! discursos do humor gráfico na Revolta da Vacina - D'Agostino Filho, Antonio (2017)
This dissertation analyzes the humorous cartoons published in several political satire newspapers in order to understand the construction of a discourse about the Vaccine Revolt and the events that surround it. For that, methodologically, were used categories borrowed from the dramaturgy, establishing the figurations as a stage in which the dramas of Rio de Janeiro of the early twentieth century are developed